Nitrogen-Passivated germanium carbide nanomeshes as potential catalysts for photocatalytic water splitting - Sarah Gamal; Ghada E. Khedr; M. Nashaat; Lobna M. Salah; Ahmed A. Maarouf; Nageh K. Allam (Scientific Reports)
Abstract Nitrogen-passivated germanium carbide (GeC) nanomeshes have been systematically investigated as efficient photocatalysts for water splitting. The nanomesh, characterized by a lattice constant of 19.3 Å and a pore diameter of 7.3 Å, maintains a planar architecture with optimized N-Ge and N-C bond lengths of 1.8 Å and 1.3 Å, respectively. Partial density of states (PDOS) analysis indicates that the conduction band is predominantly governed by Ge states, while C states dominate the valence band. Nitrogen incorporation critically alters the electronic structure near the band edges, significantly influencing photocatalytic behavior. Notably, introducing porosity reduces the bandgap from 2.04 eV (pristine GeC) to 1.33 eV in the N-passivated configuration. The calculated band edge positions straddle the redox potentials of water, indicating thermodynamic feasibility for overall water splitting. Several favorable sites were identified for the hydrogen evolution reaction (HER), with nearly thermoneutral ΔG values, suggesting high catalytic efficiency. For the oxygen evolution reaction (OER), the formation of OH* was determined to be the rate-limiting step with a ΔG1 = 1.84 eV. Bader charge analysis confirmed electron transfer from the OH* species to the adjacent Ge atom, resulting in a net gain of 0.39 |e| by Ge. These findings demonstrate that N-passivated GeC nanomeshes exhibit a favorable electronic structure and catalytic surface characteristics for photocatalytic water splitting.